KEMAMPUAN GURU IPS DALAM MENGADAKAN VARIASI MENGAJAR DI KELAS VII SMPN 14 PADANG - Putra, Miko Windra; Nazmi, Ranti; Kaksim, Kaksim (Pendidikan Sejarah, 2013)
ABSTRACTThis research represent research of study evaluate with analysis qualitative with research in SMPN 14 Field. As for informan in this research cover teachers of IPS amounting to 2 people, student and headmaster of observation technique, document study and interview through RPP. Accuracy of data tested by using data triangulation, of gathered to be data to be analysed with model of interaktif which consist of data collecting, data discount, presentation of data and withdrawal of conclusion. From result of research indicate that, style variation of teach that is: 1). Variation of Voice, pursuant to performed by research is writer seen that variation of voice taken as by teacher in SMP N 14 Field uncommitt better. This matter because of taught items many and ran against time by general examination which closer, 2). Concentration of attention of student emphasis, pursuant to performed a by research is writer seen that emphasis which is learn to uncommitt better. This matter because of teacher assume that emphasis do not too important, because each;every student have guide-book in the form of LKS (Spread sheet Student), 3). Silence dumbness of teacher, pursuant to result of conducted by research is writer, hence silence or dumbness of teacher have walked better, 4). Performing a approach contact, pursuant to result of conducted by research is writer, got that approach contact which is to learn have been executed though once in a while terpana at is one way, this matter because of to be all student pay attention Iesson better or more focus in following Iesson, 5). Sport and teacher face mimick, pursuant to conducted by research is writer seen that, body movement and mimick have been executed better, 6). Commutation of teacher position, pursuant to conducted by research is writer, commutation of teacher position uncommitt better, this matter because of teacher less comprehending about commutation of position in course of learning to teach. Keyword: variation, teach, commutation